COVID-19 related differences in the uptake and effects of internet-based cognitive behavioural therapy for symptoms of obsessive-compulsive disorder. Issue 2 (10th March 2022) - Li, Ian; Millard, Michael; Haskelberg, Hila; Hobbs, Megan; Luu, John; Mahoney, Alison
Abstract: Background: The impacts of COVID-19 for people with obsessive-compulsive disorder (OCD) may be considerable. Online cognitive behavioural therapy (iCBT) programmes provide scalable access to psychological interventions, although the effectiveness of iCBT for OCD during COVID-19 has not been evaluated. Aim: This study investigated the uptake and effectiveness of iCBT for OCD (both self- and clinician-guided courses) during the first 8 months of the pandemic in Australia (March to October 2020) and compared outcomes with the previous year. Method: 1, 343 adults (824/1343 (61.4%) female, mean age 33.54 years, SD = 12.00) commenced iCBT for OCD (1061 during the pandemic and 282 in the year before) and completed measures of OCD (Dimensional Obsessive-Compulsive Scale) and depression (Patient Health Questionaire-9) symptom severity, psychological distress (Kessler-10), and disability (WHO Disability Assessment Schedule) pre- and post-treatment. Results: During COVID-19, there was a 522% increase in monthly course registrations compared with the previous year, with peak uptake observed between April and June 2020 (a 1191% increase compared with April to June 2019). OCD and depression symptom severity were similar for the COVID and pre-COVID groups, although COVID-19 participants were more likely to enrol in self-guided courses (versus clinician-guided). In both pre- and during-COVID groups, the OCD iCBT course was associated with medium effect size reductions in OCD ( g = 0.65–0.68) and depression symptom severity ( g = 0.56–0.65), medium to large reductions in psychological distress ( g = 0.77–0.83) and small reductions in disability ( g = 0.35–.50). Conclusion: Results demonstrate the considerable uptake of online psychological services for those experiencing symptoms of OCD during COVID-19 and highlight the scalability of effective digital mental health services.